Chemical characterization and antioxidant activity of fermented beverages from the fruits of Passiflora nitida Kunth - Oliveira, Edinilze Souza Coelho; Pereira, Zilanir Carvalho; Ferreira, Alessandra Silva; Corrêa, Renilto Frota; Machado, Marcos Batista; Sanches, Edgar Aparecido; Campelo, Pedro Henrique; Barroso, Hiléia dos Santos; Boeira, Lúcia Schuch; Bezerra, Jaqueline de Araújo (Food Science and Technology, 2025)
Passiflora nitida Kunth is a wild plant species, commonly known as “wild passion fruit” in the northern region of Brazil. The fresh fruit is consumed and sold in Manaus, Amazonas. Due to its nutraceutical potential, this study aimed to produce fermented beverages from the fruit pulp using four types of commercial yeasts and two filtration parameters. Additionally, physicochemical parameters, chemical profile analyses, total phenolic content, and radical scavenging capacity were evaluated. Nuclear magnetic resonance (NMR) analyses allowed for the identification of 16 compounds in total. Among these were citric, malic, and succinic acids, L-alanine, methionine, proline, threonine, tyrosine, vitexin, and choline. Furthermore, the fermented beverages produced by Cuvée and Maestoso yeasts (unfiltered) exhibited greater sweetness, justified by lower acidity and higher soluble solids content. The beverage produced with Cuvée yeast (unfiltered) showed a high radical scavenging capacity for 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS●+) (712.0 ± 5.0 mmol TE g⁻¹, p < .05) and 2,2-diphenyl-1-picrylhydrazyl (DPPH●) (344.6 ± 16.1 mmol TE g⁻¹) compared to the juice (p > .05). Therefore, we suggest that the fermented beverage obtained from Cuvée yeast may provide health benefits and be an alternative for the region’s economic development.